The productive chain of the wood industry of Santiago del Estero (Argentina) - Schimpf, Rolando; Sánchez Ugalde, Rocío; Ludueña, Myriam; Coronel de Renolfi, Marta (Ingeniería Solidaria, 2019)
Introduction: this article is a product of research. The case of the forest species of Santiago del Estero, developed at the National University of Santiago del Estero in the period 2016-2017.Objective  to describe the productive chain of the forest industry of the province of Santiago del Estero, with emphasis on the chain of wood and furniture, and identify the critical factors for its performance.Methodology: to examine the productive chain, it is applied to the diagnostic analysis through bibliographic review and information gathering in the field; and in order to identify critical factors of the chain, a SWOT analysis was carried out.Results: in the forestry-industrial chain there is a close connection between the link of primary production and the following ones, given that the links of the first and second transformations of wood of local origin as the main source of supply.Conclusions: the forest-industrial chain originating in native forests has continuity in all the productive links. The high degree of information that refers to the productive activities, as well as the individualistic culture, the behaviors of the direct actors, do not allow generating integration processes. Weaknesses and threats are identified throughout the chain’s linkage. However, there are strengths and opportunities to enhance and capitalize. Originality: there is no background of published works on the subject for the province. Limitations: insufficient public and private information on the subject.
Keywords: productive chain; wood industry; strengths and weaknesses; timber SMEs